Is peer review evolving in the open access environment? A survey of Croatian open access journals - Stojanovski, Jadranka; Hebrang Grgić, Ivana (Septentrio Conference Series, 2017)
Most of the journals in Croatia adopted the open access (OA) model and their content is freely accessible and available for reuse without restrictions except that attribution be given to the author(s) and journal. There are 444 Croatian scholarly, professional, popular and trade OA journals available in the national repository of OA journals Hrcak, and 217 of them use peer review process as the primary quality assurance system. The goal of our study was to investigate the peer review process used by the Croatian OA journals and the editors’ attitude towards open peer review. An online survey was sent to the Hrcak journal editors with 39 questions grouped in: journal general information, a number of submitted/rejected/accepted manuscripts and timeliness of publishing, peer review process characteristics, instructions for peer reviewers and open peer review. Responses were obtained from 152 editors (141 complete and 11 partial). All journals employ peer review process except one. The data were collected from February to July 2017. The majority of journals come from the humanities (n=50, 33%) and social sciences (n=37, 24%). Less represented are journals from the field of biomedicine (n=22, 14%), technical sciences (n=16, 11%), natural sciences (n=12, 8%), biotechnical sciences (n=10, 7%) and interdisciplinary journals (n=3, 2%). Average journal submission is 54 manuscripts per year, but there are big differences among journals: maximum submission is 550 manuscripts, and minimum just five. In average journal publishes 23 papers after the reviewers’ and editors’ acceptance. In average it takes 16 days for sending the manuscript to the reviewer, 49 days for all the reviewers to send the journal a detailed report on the manuscript, 14 days to the editors’ decision, and another 60 days for the paper to be published. External peer review process where reviewers are not members of the editorial board or employees of the journal’s parent institution was used by 86 journals (60%). Other journals use external peer review process where reviewers are not members of the editorial board but could be employees of the journal’s parent institution (n=40, 28%), and editorial peer review. Remaining 10% journals combine previous three types of the peer review. Only 20% journals use exclusively reviewers from abroad, 44% are combining international and national reviewers, and 36% journals use only reviewers from Croatia. The majority of journals provide two reviews for each manuscript, and the process is double blind. Detailed instructions for peer reviewers are provided by less than half of the journals (n=57, 40%), but ethical issues like plagiarism, conflict of interest, confidentiality etc., are neglected. Usually, a reviewer is not informed of the final decision upon the manuscript, and reviews are not shared among reviewers. Somehow surprising was the opinion of the majority of the editors that reviewers must get credit for their efforts (n=121, 85%). On the other hand, editors are not familiar with the concept of open peer review, which can be easily used for that purpose. Some editors believe that open peer review is related to the identity disclosure: both authors’ and reviewers’ (n=35, 25%), reviewers’ (n=27, 19%), and authors’ identity (n=14, 10%). For many editors open peer review implies publicly available reviews (n=65, 36%) and authors’ responses (n=46, 33%). Open peer review is an unknown concept for some editors (n=32, 23%). In spite of all criticism traditional peer review is predominant in Croatian OA journals. Our findings show that traditional peer review is still the preferred review mechanism for the majority of journals in the study.